1987
DOI: 10.1111/j.1476-5381.1987.tb11311.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of prostaglandin dehydrogenase (Ph CL 28A and Ph CK 61A) increase output of prostaglandins from rat isolated lung

Abstract: 1 Two potent inhibitors ofprostaglandin dehydrogenase (PGDH), Ph CL 28A and Ph CK 61A, have been investigated for their effects on prostaglandin catabolism and synthesis in rat isolated lung.2 Both CL 28A (0.3 I1M) and CK 61A (0.5 and 5 FM) markedly increased the survival ofprostaglandin E2 (PGE2) and PGF2, on a single passage through the pulmonary circulation.3 Both inhibitors delayed the efflux of 14C following injection of ["CJ-PGE2 through the pulmonary circulation.4 Output ofPGE2 and PGF2. but not that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…They are also in agreement with the results of Mullane & Moncada (1980) who showed that captopril potentiated the release of PGI2 by Bk in dogs. The possibility that captopril enhances eicosanoid output by inhibition of prostaglandin dehydrogenase (Bakhle & Pankhania, 1987) is unlikely since it did not alter eicosanoid release after AA.…”
Section: Discussionmentioning
confidence: 99%
“…They are also in agreement with the results of Mullane & Moncada (1980) who showed that captopril potentiated the release of PGI2 by Bk in dogs. The possibility that captopril enhances eicosanoid output by inhibition of prostaglandin dehydrogenase (Bakhle & Pankhania, 1987) is unlikely since it did not alter eicosanoid release after AA.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were anaesthetized as before, the chest opened and the pulmonary artery cannulated and perfused with warmed (370C) and gassed (95% 02 + 5% C02) Krebs solution at a constant rate of 8 ml min-' as described previously (Bakhle et al, 1969 (Watts et al, 1982) and antisera (Bakhle & Pankhania, 1987) described previously. The lower limit of detection for PGE2 was 80pgml-1 and cross-reactivities were: PGE1 26%, PGF2a The total white blood cell count showed an earlier response to endotoxin (Table 1), falling to about 50% by 2h with a minimum value of just over 30% at 4 h. The total white blood cell count returned to normal by 28 h. The numbers of PMNs were also severely reduced (less than 25% of normal at 4 h) and remained low until 28 h. The proportion of PMNs in the total white blood cells also fell after endotoxin, from about 22% in untreated rats to 15% at 4 h, showing the relatively greater effect on these leukocytes.…”
Section: Pharmacokinetic Measurementsmentioning
confidence: 99%